Assessment of glucose-6-phosphate dehydrogenase activity using CareStart G6PD rapid diagnostic test and associated genetic variants in Plasmodium vivax malaria endemic setting in Mauritania - (:unkn) unknown (My University, 2019)
BackgroundPrimaquine is recommended by the World Health Organization (WHO) for radical treatment of Plasmodium vivax malaria. This drug is known to provoke acute hemolytic anemia in individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency. Due to lack of data on G6PD deficiency, the use of primaquine has been limited in Africa. In the present study, G6PD deficiency was investigated in blood donors of various ethnic groups living in Nouakchott, a P. vivax endemic area in Mauritania.Methodology/Principal findingsVenous blood samples from 443 healthy blood donors recruited at the National Transfusion Center in Nouakchott were screened for G6PD activity using the CareStart G6PD deficiency rapid diagnostic test. G6PD allelic variants were investigated using DiaPlexC G6PD genotyping kit that detects African (A-) and Mediterranean (B-) variants. Overall, 50 of 443 (11.3%) individuals (49 [11.8%] men and 1 [3.7%] woman) were phenotypically deficient. Amongst men, Black Africans had the highest prevalence of G6PD deficiency (15 of 100 [15%]) and White Moors the lowest (10 of 168, [5.9%]). The most commonly observed G6PD allelic variants among 44 tested G6PD-deficient men were the African variant A- (202A/376G) in 14 (31.8%), the Mediterranean variant B- (563T) in 13 (29.5%), and the Betica-Selma A- (376G/968C) allelic variant in 6 (13.6%). The Santamaria A- variant (376G/542T) and A variant (376G) were observed in only one and two individuals, respectively. None of the expected variants was observed in 8 (18.2%) of the tested phenotypically G6PD-deficient men.ConclusionThis is the first published data on G6PD deficiency in Mauritanians. The prevalence of phenotypic G6PD deficiency was relatively high (11.3%). It was mostly associated with either African or Mediterranean variants, in agreement with diverse Arab and Black African origins of the Mauritanian population.
Keywords: African Research